THE EDUCATIONAL VALUES OF THE MAIN CHARACTER IN BEAUTIFUL MIND FILM - Simanjuntak, Marudut Bernadtua (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
Abstract. This study aims to describe the educational values of the main character in a Film Beautiful Mind. The study was compiled with a qualitative approach. Data was collected by watching and recording and analyzed by qualitative narrative approaches. The results showed that there are 6 educational values of the main character in the Film Beautiful Mind, including: (1) hard work, (2) creative, (3) love for the country, (4) friendly / communicative, (5) social and (6) appreciate achievement. Based on the findings in this study, Film Beautiful Mind deserves to be used as a spectacle for motivation and inspiration because it contains many educational values.